Penerapan Strategi Poster Comment Untuk Meningkatkan Keaktifan Dan Hasil Belajar PPKn Siswa SMP Negeri 1 Kabupaten Bungo - Dedek Helida Pitra; Khairul Saleh (Yayasan Literasi Sains Indonesia, 2022)
The application of the poster comment strategy has the aim of knowing the active learning process and learning outcomes after the implementation of this strategy. Furthermore, the application of the poster comment strategy can increase student activity and learning outcomes. This research approach is a qualitative description and the type of research is Classroom Action Research (CAR). In this study, the researcher acts as a teacher and also as an observer. The research was carried out for 2 cycles. Data collection techniques were carried out by means of an observer (observer), measurement of learning outcomes and documentation. The learning process of Pancasila and Citizenship Education in class VIIA before using the poster comment strategy was found to have low student responses and tend to be bored with learning so that it did not affect learning outcomes optimally. The application of the poster comment strategy was carried out by students commenting on images related to Civics Education material. The implication of the implementation of CAR from the first cycle to the second cycle is that students look more enthusiastic and active in learning, student learning outcomes have increased significantly. In addition to increasing learning outcomes, this strategy makes students active in learning, especially Civics.